(х-16)*9=126
х-16=126:9
х-16=14
х=16+14
х=30
28*(х+5)=224
х+5=224:28
х+5=8
х=8-5
х=3
(х+76):7=15
х+76=15*7
х+76=105
х=105-76
х=29
144:(х-3)=36
х-3=144:36
х-3=4
х=4+3
х=7
(х+67):18=4
х+67=18*4
х+67=72
х=72-67
х=5

Ответы и объяснения

2013-10-02T14:57:39+04:00
X-16)*9=126
x-16=126:9
x-16=14
x=14+16
x=30
28*(x+5)=224
x+5=224:28
x+5=8
x=8-5
x=3
(x+76):7=15
x+76=15*7
x+76=105
x=105-76
x=29
144:(x-3)=36
x-3=144:36
x-3=4
x=4+3
x=7
21*(y-8)=84
y-8=84:21
y-8=4
y=8+4
y=12
(x+67):18=4
x+67=4*18
x+67=72
x=72-67
x=5